PERAN KOMUNIKASI ANTARPRIBADI PELATIH DALAM MENINGKATKAN KETANGGUHAN MENTAL ATLET (STUDI PADA PELATIH DAN ATLET KARATE KUMITE JUNIOR GOKASI JAKARTA BARAT) - Fifi Zuniarti (2021)
The direct championship which was participated by the West Jakarta Gokasi team through the DKI Jakarta Gokasi team was the 2019 Gokasi National Championship in Cirebon, West Java. According to data provided by the West Jakarta technical committee, West Jakarta Gokasi managed to donate medals in the kumite class, namely 16 medals consisting of 9 gold medals, 2 silver medals and 5 bronze medals. However, according to data, the junior kumite class has the lowest achievement compared to other kumite classes such as cadets. While the two classes came from the same kumite coach, they produced different results and also experienced communication barriers. This research aims to determine the role of coach interpersonal communication in improving the mental toughness of kumite athletes and what are the barriers to communication in improving performance. This research is a qualitative research with the approach method used is phenomenology. Through interviews and observations that have been made, it is found that the social penetration theory has 4 stages of the process where cadet kumite athletes enter the stable exchange stage while junior kumite athletes are in the affective exchange process stage. The role of the coach's interpersonal communication is to convince through words that have an impact on athletes, provide verbal and nonverbal support, provide examples during training as a match evaluation and provide solutions. Communication barriers that occur are athletes' intelligence in understanding and easily divided focus, physical and semantic